A method for predicting deep mining subsidence considering secondary compression of composite lithology gangue
By calculating the top plate deflection and sinking curve of the composite lithologic gangue filling body, combined with the theory of random medium, the problem of insufficient prediction accuracy of deep filling and recovery subsidence in the existing technology is solved, and a more accurate subsidence prediction effect is achieved.
Patent Information
- Application Number
- CN202411721100.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-11-28
AI Technical Summary
In the prior art, when predicting the secondary compression deformation of composite lithologic gangue fillings under deep filling conditions and their impact on surface subsidence, the accuracy is insufficient and the settlement situation cannot be accurately predicted.
By calculating the deflection of the top plate of the collapsed goaf and the filled goaf, the sinking curve of the giant thick sandstone was obtained based on similar principles, and the sinking curve of the topsoil layer was obtained based on the random medium theory, so as to achieve the deep filling and subsidence prediction of the secondary compression of composite lithologic gangue.
This method can accurately calculate the deflection deformation of the goaf top plate and pass it to the huge thick sandstone surface through similar theories, which differently transfers the sinking space, improving the accuracy of subsidence prediction. The difference between the numerical model and the actual results is only 10mm.
Smart Images

Figure CN119203859B_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a deep mining subsidence prediction method taking into account secondary compression of composite lithology gangue, and belongs to the technical field of subsidence prediction. Background Art
[0002] At present, the research on the surface subsidence prediction model of backfill mining is mainly focused on the middle and shallow backfill mining. The main research methods include the mechanical model of multiple medium coupling and the probability integral method based on equivalent mining height and parameter correction. However, with the increase of backfill depth, the composite lithology gangue backfill body will be significantly compressed and deformed under the influence of high ground stress. Under the additional influence of water environment such as water accumulation in the goaf, the gangue blocks are more easily broken and the gangue particles slide relatively, which will cause significant secondary compression deformation of the gangue backfill body. This situation makes the surface subsidence prediction model of backfill mining in the existing technology insufficiently accurate and unable to perform settlement prediction according to expected requirements. Summary of the invention
[0003] The purpose of the present invention is to provide a deep mining subsidence prediction method taking into account the secondary compression of composite lithology gangue, so as to solve the problem of inaccurate subsidence prediction results in the prior art.
[0004] A deep mining subsidence prediction method taking into account the secondary compression of composite lithology gangue is proposed. The deflection of the overlying roof of the collapsed goaf and the filled goaf is calculated. The subsidence curve of the thick sandstone is obtained based on the similarity principle. The subsidence curve of the topsoil layer is obtained by combining the random medium theory. The coordinate value of any point on the x-axis is substituted to obtain the corresponding subsidence value of the topsoil layer, thereby realizing subsidence prediction.
[0005] The calculation of the deflection of the overlying roof of the collapsed goaf and the filled goaf includes: the deflection curve of the overlying roof of the filled goaf is: , the deflection curve of the overlying roof in the collapsed goaf is :
[0006] ; ;
[0007] In the formula, is half the length of the filling surface, is the bending stiffness of the roof, and the load of the rock layer from the top of the roof to the surface is called the equivalent deadweight load acting on the top of the roof , is the elastic coefficient of the filling body, is the elastic coefficient of coal, For the point Coordinates on the axis.
[0008] Solution and :
[0009] ;
[0010] ;
[0011] ; ;
[0012] In the formula, is a natural constant, is the characteristic coefficient of the filling body, is the characteristic coefficient of coal body, , , , , , , , There are 8 undetermined coefficients.
[0013] The equations and boundary conditions for rotation, bending moment, and shear are combined to solve for the top plate deflection.
[0014] The equations for rotation angle, bending moment and shear force include: The rotation angle equation below the overlying roof in the filling goaf is: The bending moment equation is The shear force equation is , the rotation angle equation below the overlying roof of the collapsed goaf is: The bending moment equation is The shear force equation is :
[0015] ; ;
[0016] ; ;
[0017] ; .
[0018] The boundary conditions include: condition 1, At infinity of the axis, the roof deflection is equal to the compression of the coal body:
[0019] ;
[0020] From condition 1, we can get .
[0021] Boundary conditions include: Condition 2, when the filling body in the mining area is fully compacted:
[0022] ; .
[0023] The boundary conditions include: Condition 3: At the same time, at the connection between the filling body and the coal body, the following continuity conditions exist:
[0024] ; ;
[0025] ; ;
[0026] The eight unknown coefficients were obtained by solving the simultaneous equations, and the deflection of the overlying roof in the collapsed goaf and the filled goaf was calculated.
[0027] The subsidence curve of extremely thick sandstone is:
[0028] ; ;
[0029] In the formula, is the horizontal coordinate transformation coefficient of the thick sandstone subsidence curve relative to the roof subsidence curve, is the horizontal coordinate of the roof subsidence boundary, is the horizontal coordinate of the boundary of the thick sandstone subsidence. and The top plate deflection is obtained by combining the two curves. .
[0030] Based on the random medium theory, the corresponding topsoil subsidence values are obtained, including: assuming that the mining depth and width are infinitely small, the unit mining-induced Settlement value at point for:
[0031] ; ;
[0032] In the formula, express The depth value corresponding to the coordinate value, is the influence radius, is the particle size connection constant;
[0033] For mining depth of the surface, , then it satisfies:
[0034] ; ; ;
[0035] In the formula, The mining depth is of the surface The settlement value corresponding to the coordinate value, is the main impact radius;
[0036] The random medium theory considers the bending and sinking of thick sandstone as the mining of medium-shallow non-uniform coal seams, and regards the area of the sinking of thick sandstone as Decompose into a finite number of infinitely small units, and regard the surface movement as the area The subsidence of the ground caused by mining in each small mining unit is superimposed. The distance from the origin on the axis is ,exist The distance from the origin on the axis is , the sinking curve of the topsoil layer for:
[0037] ;
[0038] In the formula, The thickness of the rock layer above the thick sandstone. The thickness of the sandstone is very thick. It is the sinking curve of the extremely thick sandstone. Move the boundary angle for the surface.
[0039] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention takes into account the secondary compression deformation of the composite rock gangue filling body under the coupling influence of high ground stress and water environment, and can accurately calculate the deflection deformation of the roof of the goaf; (2) The roof deflection deformation is transferred to the thick sandstone surface through the similarity theory, and the bending and sinking of the thick sandstone is regarded as the mining of medium and shallow non-uniform coal seams, thereby realizing the differentiated transmission of the sinking space in the bedrock layer and the topsoil layer. Among them, the calculation model of the sinking space of the thick sandstone surface is derived in combination with the similarity theory, and the difference between the calculation result of the numerical model (the model has passed the reliability verification) is only 10 mm. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is the loading curve of single gangue with different particle sizes;
[0041] Figure 2 It is the stress-strain curve of different gradations;
[0042] Figure 3 It is the stress-strain curve of composite lithology gangue;
[0043] Figure 4 This is the particle size ratio diagram of oil shale (30mm) before and after loading;
[0044] Figure 5 This is the particle size ratio diagram of oil shale (20mm) before and after loading;
[0045] Figure 6 This is the particle size ratio diagram of medium sandstone (30mm) before and after loading;
[0046] Figure 7 This is the particle size ratio diagram of medium sandstone (20 mm) before and after loading;
[0047] Figure 8 This is the change diagram of graded gangue crushing;
[0048] Fig. 9 This is the composite lithology gangue crushing change diagram;
[0049] Fig.10 This is a schematic diagram of the waterlogged gangue accounting for 0%;
[0050] Fig.11 This is a schematic diagram of the case where waterlogged gangue accounts for 25%;
[0051] Fig.12 This is a schematic diagram of the case where waterlogged gangue accounts for 50%;
[0052] Fig.13 This is a schematic diagram of the case where the proportion of waterlogged gangue is 100%;
[0053] Fig.14 This is a single gangue immersion test diagram;
[0054] Fig.15 This is the experimental diagram of water content of composite lithology gangue;
[0055] Fig.16 The stress-strain curve of the composite lithology gangue water immersion experiment;
[0056] Fig.17 It is the water percentage-strain curve of the composite lithology gangue water percentage experiment;
[0057] Fig.18 This is a single waterlogged gangue crushing characteristic diagram;
[0058] Fig.19 It is the characteristic diagram of rock gangue immersion time and crushing characteristics;
[0059] Fig. 20 This is the analysis diagram of the lithology gangue water soaking time and crushing;
[0060] Fig.21 This is the crushing characteristic diagram of the proportion of lithologic gangue soaked in water;
[0061] Fig. 22 This is the analysis diagram of the proportion of rock gangue soaked in water and broken;
[0062] Fig.23 It is a spatial calculation model for the subsidence of extremely thick sandstone;
[0063] Fig.24 It is a theoretical model for granular media;
[0064] Fig.25 is the probability distribution of particle movement;
[0065] Fig.26 This is a schematic diagram for predicting uneven subsidence of the topsoil layer;
[0066] Fig. 27 The calculation results of roof subsidence in deep filling mining;
[0067] Fig.28 It is the fitting result of the subsidence boundary and the distance from the coal seam;
[0068] Fig.29 This is the calculation result of the subsidence space of extremely thick sandstone;
[0069] Fig.30 It is the fitting result of the subsidence boundary and the distance from the coal seam;
[0070] Fig.31 Calculation result of ground subsidence. DETAILED DESCRIPTION
[0071] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, but not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0072] A deep mining subsidence prediction method taking into account the secondary compression of composite lithology gangue is proposed. The deflection of the overlying roof of the collapsed goaf and the filled goaf is calculated. The subsidence curve of the thick sandstone is obtained based on the similarity principle. The subsidence curve of the topsoil layer is obtained by combining the random medium theory. The coordinate value of any point on the x-axis is substituted to obtain the corresponding subsidence value of the topsoil layer, thereby realizing subsidence prediction.
[0073] The calculation of the deflection of the overlying roof of the collapsed goaf and the filled goaf includes: the deflection curve of the overlying roof of the filled goaf is: , the deflection curve of the overlying roof in the collapsed goaf is :
[0074] ; ;
[0075] In the formula, is half the length of the filling surface, is the bending stiffness of the roof, and the load of the rock layer from the top of the roof to the surface is called the equivalent deadweight load acting on the top of the roof , is the elastic coefficient of the filling body, is the elastic coefficient of coal, For the point Coordinates on the axis.
[0076] Solution and :
[0077] ;
[0078] ;
[0079] ; ;
[0080] In the formula, is a natural constant, is the characteristic coefficient of the filling body, is the characteristic coefficient of coal body, , , , , , , , There are 8 undetermined coefficients.
[0081] The equations and boundary conditions for rotation, bending moment, and shear are combined to solve for the top plate deflection.
[0082] The equations for rotation angle, bending moment and shear force include: The rotation angle equation below the overlying roof in the filling goaf is: The bending moment equation is The shear force equation is , the rotation angle equation below the overlying roof of the collapsed goaf is The bending moment equation is The shear force equation is :
[0083] ; ;
[0084] ; ;
[0085] ; .
[0086] The boundary conditions include: condition 1, At infinity of the axis, the roof deflection is equal to the compression of the coal body:
[0087] ;
[0088] From condition 1, we can get .
[0089] Boundary conditions include: Condition 2, when the filling body in the mining area is fully compacted:
[0090] ; .
[0091] The boundary conditions include: Condition 3: At the same time, at the connection between the filling body and the coal body, the following continuity conditions exist:
[0092] ; ;
[0093] ; ;
[0094] The eight unknown coefficients were obtained by solving the simultaneous equations, and the deflection of the overlying roof in the collapsed goaf and the filled goaf was calculated.
[0095] The subsidence curve of extremely thick sandstone is:
[0096] ; ;
[0097] In the formula, is the horizontal coordinate transformation coefficient of the thick sandstone subsidence curve relative to the roof subsidence curve, is the horizontal coordinate of the roof subsidence boundary, is the horizontal coordinate of the boundary of the thick sandstone subsidence. and The top plate deflection is obtained by combining the two curves. .
[0098] Based on the random medium theory, the corresponding topsoil subsidence values are obtained, including: assuming that the mining depth and width are infinitely small, the unit mining-induced Settlement value at point for:
[0099] ; ;
[0100] In the formula, express The depth value corresponding to the coordinate value, is the influence radius, is the particle size connection constant;
[0101] For mining depth of the surface, , then it satisfies:
[0102] ; ; ;
[0103] In the formula, The mining depth is of the surface The settlement value corresponding to the coordinate value, is the main impact radius;
[0104] The random medium theory considers the bending and sinking of thick sandstone as the mining of medium-shallow non-uniform coal seams, and regards the area of the sinking of thick sandstone as Decompose into a finite number of infinitely small units, and regard the surface movement as the area The subsidence of the ground caused by mining in each small mining unit is superimposed. The distance from the origin on the axis is ,exist The distance from the origin on the axis is , the sinking curve of the topsoil layer for:
[0105] ;
[0106] In the formula, The thickness of the rock layer above the thick sandstone. The thickness of the sandstone is very thick. It is the sinking curve of the extremely thick sandstone. Move the boundary angle for the surface.
[0107] The present invention first studies the proportioning scheme of composite lithology gangue. When filling deep goaf, bulk gangue will be subject to the huge pressure of the overlying rock strata, as well as the influence of water accumulation formed by water gushing from the aquifer to the goaf through the fracture zone. In order to better study the compaction characteristics of composite lithology gangue during the compaction process and the influence of water accumulation on the mechanical properties of gangue, the influence of composite lithology gangue bearing capacity is studied by introducing the preparation of gangue materials, the optimization of gangue under the influence of various factors, and the mechanical properties of gangue under the influence of water environment.
[0108] It is planned to select gangue and test its physical and mechanical properties. In the selection and preparation of gangue, composite lithology gangue including medium sandstone of coal mine is selected. The crusher used is 100*150 jaw crusher, the motor is 1400 rpm, and the power reaches 2.2 kilowatts, which can crush the gangue particles into small particles of 0-30mm. After the gangue is crushed, standard square hole stone screens with sizes of 5mm, 10mm, 15mm, 20mm, and 30mm are used to screen out gangue groups of different particle sizes such as 0mm-5mm, 5mm-10mm, 10mm-15mm, 15mm-20mm, and 20mm-30mm.
[0109] In the study of the basic properties of gangue filling materials, for the density of single particles, the mass and volume of the gangue were measured using a precision electronic scale and a measuring cylinder. In order to eliminate the accidental error in the experiment, 10 gangue particles with particle sizes ranging from 20 to 40 mm were randomly selected. After multiple measurements and the average value was calculated, the final density of the gangue was determined. :
[0110] ; ;
[0111] In the formula, each group of gangue is numbered as , For the The density of gangue, is the quality of gangue, is the total volume after immersion in water, is the volume of water before immersion, , is the number of gangue.
[0112] In the final density measurement results, the density of oil shale gangue is 1.949g / cm 3 ~2.500g / cm 3 The average density is 2.200 g / cm 3 ; The density of medium sandstone gangue is 2.158g / cm 3 ~2.729g / cm 3 The average density is 2.480g / cm 3 , the average density of oil shale is slightly smaller than that of medium sand.
[0113] The bulk density refers to the mass per unit volume of bulk materials in a stacked state. Considering the internal voids in the stacked particles, it is usually smaller than the density of individual particles. In subsequent compression experiments, the bulk density is selected as the actual density for calculation:
[0114] ;
[0115] In the formula, is the bulk density, is the mass of bulk gangue, is the volume of loose gangue.
[0116] The single gangue with different particle size combinations is randomly selected and slowly dropped from above into the loading cylinder and gradually filled and leveled. The volume of the gangue is 4417.9cm 3 , and then weigh its mass. In order to eliminate accidental errors, five groups of experiments were conducted to obtain the average value as the bulk density, and three decimal places were retained. The particle density is generally larger than the bulk density, which is 1.76 to 1.87 times the bulk density. The average bulk density of oil shale is 1.244 g / cm 3 The average bulk density of medium sandstone is 1.325 g / cm 3 .
[0117] Moisture content In the determination, the filling gangue will be affected by the water environment, which will affect its compressive strength. The common method for experimental determination of the moisture content of gangue is the drying method. First, gangue of different particle size ranges is put into water (no less than 100g), and soaked in water for a certain period of time according to the experimental design, and the mass is weighed. Then put it into the dryer, set the temperature to 105℃-110℃, dry it to constant weight, and weigh the mass , the moisture content is:
[0118] ;
[0119] In the selection of composite lithology gangue ratio under high ground stress environment, the overall change of loose graded gangue as filling material can be roughly simplified as the surrounding rocks on both sides are fixed, and the huge pressure brought by the overlying rock strata produces a vertical compression mode. This section studies the bearing characteristics under different gangue particle sizes, gradations, and composite lithology gangue ratios through physical experiments, and selects the composite lithology gangue ratio scheme under the optimal gradation.
[0120] According to the measured high-ground stress environment in deep coal mines, the simulated high-ground stress size is selected to be 20MPa, the loading method is stress loading, and the loading speed is 1KN / S. The maximum particle size of this experiment is 30mm. According to the principle that the inner diameter of the cylinder is not less than 5 times the maximum particle size, the inner diameter of the loading cylinder is designed to be 150mm and the cylinder height is 300mm. The cylinder material is 45# steel. Since the pressure servo stress needs to be set to 20MPa, the strength and wall thickness of the customized cylinder need to be calculated. Taking the lateral pressure coefficient as 0.7, the internal pressure is 14MPa, the yield strength of 45# steel is 355MPa, and the safety factor is 0.2, then the surface stress of the cylinder is 177.5Mpa. The surface tension of the cylinder wall can be obtained from the elastic mechanics formula :
[0121] ;
[0122] In the formula, is the internal pressure, is the inner radius of the cylinder, is the outer radius of the cylinder, is the position of any distance from the cylinder to the center of the circle; when = When the tensile stress is maximum :
[0123] ;
[0124] When the maximum tensile stress on the cylinder surface is 177.5MPa, the inner diameter is 150mm and the outer diameter is 162.34mm, while the customized cylinder outer diameter is 194mm, which can meet the loading requirements.
[0125] In the selection method of composite lithology gangue under high ground stress environment, in order to determine the optimal composite lithology gangue ratio under high ground stress environment, the influence of the maximum particle size (20mm, 30mm) is first determined by single lithology gangue (oil shale and medium sandstone), and then the optimal particle size is selected to determine the influence of particle grading on the bearing capacity of gangue and the optimal grading is selected. Finally, the optimal gangue ratio is determined through 4 groups of composite lithology gangue ratio experiments. In current research, Talbot theory is often introduced as the basis for gangue grading. Talbot theory believes that when the grading curve is closer to a parabola, the density of the aggregate is greater, so that better mechanical properties and stability can be obtained. The formula is as follows:
[0126] ;
[0127] In the formula, For particles smaller than the specified particle size ( )’s mass fraction, is the particle size of gangue particles, is the maximum particle size of the gangue particles, is the Talbot coefficient.
[0128] First, the optimal particle size of single-graded gangue is determined. Under the premise of a gradation coefficient of 0.3, two types of lithologic gangue loading experiments with maximum particle sizes of 20mm and 30mm are designed, and oil shale and medium sandstone are loaded respectively. After determining the optimal particle size, four gradation coefficients of 0.3, 0.4, 0.5, and 0.6 are designed to load the gangue with the optimal particle size to determine the optimal gradation selection, a total of 4 groups of experimental specific plans. After obtaining the results of the two influencing factors of gangue particle size and gradation in the above experiment, the ratio of composite lithologic gangue is determined. Experimental groups A1 and A2 are designed to form a skeleton with mixed lithologic gangue with a particle size of 5-30mm, and oil shale is used as fine aggregate to fill the voids. Similarly, experimental groups A3 and A4 use medium sandstone as fine aggregate to fill the voids on the basis of different skeleton mixtures, and analyze the bearing capacity of composite lithologic gangue, a total of 4 groups of experimental specific plans. In the loading experiment of composite lithology gangue under high ground stress environment, the stress-strain curves of different lithology gangue loading were studied. Based on the above experimental scheme, the loading experiment was carried out and the characteristic law of the stress-strain curve of the sample was analyzed. Under the condition of lateral confinement compression, the sample strain can be regarded as the ratio of vertical displacement to sample height, and the stress can be obtained by converting the loading force to the cylinder area:
[0129] ; ;
[0130] In the formula, is the specimen strain, is the initial sample height, in mm, is the compression amount of the sample, in mm, is the stress of the sample, in MPa, The force applied by the electro-hydraulic servo biaxial shear tester, in KN, is the inner radius of the cylinder, in mm.
[0131] The loading experiment of single gangue with different particle sizes is divided into two types: the maximum particle size is 20mm and 30mm. The lithology is divided into two types: oil shale and medium sandstone. The loading is carried out according to the gradation coefficient of 0.3. The stress-strain curve is shown in the figure. Figure 1 As shown. Figure 1 It can be seen that the strain rate of the gangue with different proportions of lithology shows a trend of first fast and then slow. When the loading stress is 0MPa-1MPa, the strain rate changes linearly at a faster rate, and there is not much difference in the changes of different particle sizes of the two lithologies. When the loading stress is 2MPa-8MPa, the strain of the sample increases rapidly, showing a nonlinear change trend, and the bearing difference of different lithologies also begins to appear. When the stress reaches 8MPa-20MPa, the strain of the sample begins to slow down, but still increases slowly until the end of loading. The stress-strain curves between different lithologies are obviously different, among which the strain of the oil shale experimental group is 0.28, and that of the medium sandstone experimental group is 0.33. The bearing capacity of oil shale is higher than that of medium sandstone, which is due to the mechanical properties and physical characteristics of the rock samples. Among them, oil shale mostly presents flat lamellae, while medium sandstone presents blocky particle shape. Therefore, although they all have the same rate of growth at the beginning of the compaction process, the lamellae shape of oil shale is arranged more densely in the subsequent compression process, which is more difficult to compress than the blocky particles of medium sandstone.
[0132] The stress-strain curves of oil shale with different loading gradations are shown in Figure 2. Figure 2 As shown in the figure, after the loading test of different lithology gangue, oil shale and 30mm particle size group were selected for subsequent optimal gradation experiment. Before the loading experiment reached 10MPa, the experimental group with gradation 0.3 had the largest compression, followed by the experimental groups with gradation 0.6 and gradation 0.5, and the experimental group with gradation 0.4 had the smallest strain; when loading 13MPa to 20MPa, the compression trend of each grade changed significantly, among which the experimental group with gradation 0.5 had the largest strain of 0.294, followed by 0.29 for gradation 0.6, 0.286 for gradation 0.3, and the smallest strain of 0.285 for gradation 0.4. It can be seen that the gangue ratio scheme with gradation 0.4 has the smallest compressive capacity, and the compressive capacity difference between gradations is not large.
[0133] After the above screening experiments, the gangue grading combination with the best compressive resistance (grading coefficient 0.4) was selected for the loading experiment of composite lithology gangue. The proportion of oil shale in the four groups of experiments was A2 (74%), A3 (51%), A1 (49%), and A4 (25%) from high to low. The stress-strain curve of composite lithology gangue loading is shown in Figure 2. Figure 3 As shown, the bearing characteristics of experimental groups A1 and A2 are higher than those of groups A3 and A4, which also shows that the bearing characteristics of oil shale are better than those of medium sandstone, verifying the experimental results of single gangue loading.
[0134] Experimental groups A1 and A2, in which oil shale is used as fine material filling, have the best bearing capacity of gangue. In the A1 experimental group, only oil shale accounts for 49% of the fine material, and the strain reaches 0.295. However, after removing the filling fine material in A2, oil shale still accounts for 25% of the mass in the particle size of 5-30mm that constitutes the skeleton. Therefore, the total proportion of oil shale in the A2 experimental group is 74%, so the minimum strain reaches 0.27.
[0135] In the experimental groups A3 and A4 with medium sandstone as fine material filling, it can be found that the A3 experimental group only has 49% of medium sandstone aggregate, and its compressive performance is better than that of the A4 experimental group, with a strain of 0.31; while A4 still has 25% of medium sandstone skeleton, and the total mass of medium sandstone accounts for 74%, so the bearing capacity is the worst, with a strain of 0.33. The four groups of experiments prove that in the ratio of composite lithology gangue, the more hard gangue accounts for, the better its bearing capacity.
[0136] The present invention selects the crushing rate B which can better reflect the crushing phenomenon of each particle size group. g The crushing rules of each particle size group in graded gangue were analyzed. The particle size ratio of oil shale (30 mm) before and after loading was as follows: Figure 4 As shown in the figure, the particle size ratio of oil shale (20 mm) before and after loading is Figure 5 As shown in the figure, the particle size ratio of medium sandstone (30 mm) before and after loading is Figure 6 As shown in the figure, the particle size ratio of medium sandstone (20 mm) before and after loading is Figure 7 shown.
[0137] From the changes in the crushing of a single gangue loading, it can be seen that the crushing rate of oil shale with a maximum particle size of 30mm is 31%, and the crushing rate of the maximum particle size of 20mm is 30%, which is not much different. In the oil shale (30mm) experimental group, the larger the particle size, the higher the crushing rate. Among them, the crushing difference of 20-30mm reached 8% at the highest. The proportion of 5mm-30mm particle size groups decreased, and the proportion of 0mm-5mm increased by 16%. For the 20mm particle size experimental group, the crushing difference of 5mm-20mm particle size was 4%-5%, which was more evenly distributed compared to the 30mm experimental group.
[0138] The crushing changes of graded gangue are as follows Figure 8 As shown by Figure 8It can be seen that the gradation also has a certain influence on the crushing of gangue. When the gradation is 0.4, the crushing rate of gangue is the lowest at 26%, so its bearing capacity is the strongest. The crushing rate of gradation 0.3 is the second highest at 31%, but because the 0mm-5mm particle size has a high proportion in the initial particle size, its bearing capacity is weaker than that of gradation 0.4. The crushing rate of the experimental group with gradation 0.6 is the highest at 34%, but because the proportion of 5mm-30mm gangue in the experimental group with gradation 0.6 is as high as 66%, the comprehensive crushing difference before and after loading is the largest, and the crushing is more sufficient in the later stage of loading. The proportion of 0mm-5mm particle size as filling fine material has increased significantly to 17%, and the bearing capacity is relatively poor. In the experimental group with gradation 0.5, the proportion of 5mm-10mm particle size increased by 2%, which is not sufficient compared with the other experimental groups. Therefore, less filling fine material converted into 0mm-5mm during loading is less, and its bearing capacity is the worst.
[0139] The crushing changes of composite lithology gangue are as follows Fig. 9 As shown by Fig. 9 Analysis of the corresponding law of composite lithology gangue on the crushing characteristics shows that the crushing rate of experimental groups A1 and A2 is significantly lower than that of experimental groups A3 and A4. The difference between the A2 and A4 experimental groups is the composition of 0mm-5mm different lithology filling fines, and the crushing contrast is more obvious. The A2 experimental group reached 20%, and the A4 experimental group reached 31%. This is because the 0mm-5mm oil shale as flaky filling fines makes the sample more compact as a whole, and the crushing rate of the composite lithology gangue after loading is small. The filling fines are mainly granular with medium sandstone. When loading, the voids in the composite lithology sample are more easily compressed, which increases the crushing rate. It is found that oil shale as filling fines can better reduce the crushing of composite lithology gangue.
[0140] Two groups of experiments were designed, with different water contents of composite lithology gangue and different proportions of water-containing gangue. The proportion of water-soaked gangue was 0%. Fig.10 As shown, waterlogged gangue accounts for 25%. Fig.11 As shown, waterlogged gangue accounts for 50% Fig.12 As shown, the proportion of waterlogged gangue is 100%. Fig.13 As shown. In order to simulate the bearing characteristics of gangue under the influence of water accumulation in the goaf, the experimental design is designed from the perspectives of time and space. For the experimental design from the time perspective, the water content of the composite lithology gangue is different through the length of immersion time, which in turn affects the physical properties of the filling gangue. Four groups of experiments are designed for immersion for 0 days, 2 days, 5 days, and 10 days; for the experimental design from the spatial perspective, in order to simulate the erosion degree of filling gangue by water accumulation in the goaf, the composite lithology gangue that has been immersed in water for 2 days is placed at the bottom of the loading cylinder and covered with gangue with natural water content. Four groups of experiments are designed with immersion ratios of 0%, 25%, 50%, and 100%. Considering the material limitations, the composite lithology gangue ratio scheme of the A1 experimental group above is selected for the experiment.
[0141] In the composite lithology gangue loading experiment with different water contents, the single gangue immersion experiment is as follows: Fig.14 As shown in the figure, when loaded with 0MPa-3MPa, the strain rate of the water-soaked gangue is the fastest and shows a linear growth type. When loaded to 3MPa-7MPa, its growth curve gradually slows down, and the curve tends to be stable until 7MPa. Among them, the strain of medium sandstone is 0.327, and it is 0.431 after 2 days of immersion; the strain of oil shale is 0.288, and it is 0.351 after 2 days of immersion. Comparing the changes of gangue before and after immersion in water, it can be obtained that the bearing capacity of the two gangues has been weakened to varying degrees after immersion in water. The strain of medium sandstone increases by 0.104, and the strain of oil shale increases by 0.063. According to the results of the immersion experiment, although oil shale has strong water absorption, its bearing capacity is stronger, and its compressive strength changes less after immersion in water.
[0142] Analysis of the changes in the loading curves of the two types of water-soaked gangue shows that the bearing capacity of oil shale is still stronger than that of medium sandstone; medium sandstone still has a small increase in the later stage of loading, while the strain of oil shale begins to stabilize when the stress reaches 10MPa, and can reach a stable state faster. Therefore, in the subsequent selection of composite lithology gangue, a proportion scheme with a larger proportion of oil shale should be selected for experiment.
[0143] For the determination of the moisture content of composite lithology gangue, considering that the sample includes two kinds of lithology gangue, the dry weight and water absorption rate of the two lithologies should be determined first during the calculation. The overall moisture content of the sample can be obtained by calculating the ratio of the mass of the overall water in the sample to the dry weight of the sample:
[0144] ;
[0145] In the formula, is the overall moisture content of the sample, is the dry weight of medium sandstone, ω1 is the water absorption rate of medium sandstone, is the dry weight of oil shale, and ω2 is the water absorption rate of oil shale. In the composite lithology gangue immersion experiment, the water content was 0% after 0 day of immersion, 10.41% after 2 days of immersion, 11.39% after 5 days of immersion, and 11.49% after 10 days of immersion.
[0146] The moisture content test of composite lithology gangue is as follows Fig.15 As shown in the figure, through experiments with different water contents, it can be seen that the strain curve trend of composite lithology water-soaked gangue is the same as that of single lithology gangue, which undergoes rapid deformation at 0MPa-3MPa and begins to enter a slow growth stage when the stress reaches 7MPa. Among them, the strain without water immersion is 0.295, the strain after 2 days of water immersion is 0.365, the strain after 5 days of water immersion is 0.388, and the strain after 10 days of water immersion is 0.389.
[0147] After 2 days of immersion, the gangue bearing capacity was greatly affected, and the strain increased by 0.07; however, the deformation difference between 2-5 days and 5-10 days was small, 0.023 and 0.001 respectively, indicating that the time period before 2 days of immersion had a greater impact on the gangue bearing capacity. By comparing the experimental groups of 10 days and 5 days of immersion, it can be found that although the strain of 10 days of immersion is the largest, the change trend is the same as that of the experimental group of 5 days of immersion, and the overall difference between the two is not large. At this time, the moisture content of the gangue in the two groups of experiments is small, which makes the strain difference small.
[0148] It can be seen that the physical properties of composite lithology gangue are most affected in the first two days of immersion. Therefore, during the filling of composite lithology gangue, if there is any influence of water environment, it is necessary to focus on checking the changes of the filling body in the early stage of immersion.
[0149] In the composite lithology gangue loading experiment under different proportions of water-containing gangue, the stress-strain curve of the composite lithology gangue water-containing proportion experiment is as follows: Fig.16 As shown in the figure, the water immersion ratio-strain curve is as follows Fig.17 As shown in the figure, through the experiment of different water-immersion ratios of composite lithologic gangue, it can be known that the strain of 0% water-immersion ratio is 0.295, the strain of 25% water-immersion ratio is 0.367, the strain of 50% water-immersion ratio is 0.37, and the strain of 100% water-immersion ratio is 0.365. 0MPa-8MPa is the stage of rapid strain increase, which is the stage with the greatest influence of water-immersion gangue ratio. At 14MPa, the strain growth rate slows down until the end of loading, and the strain increases with the increase of water-immersion gangue ratio; and when the proportion of water-containing gangue is greater than 25%, its final strain will not change much. When the experimental stress reaches 20MPa, its strain tends to be stable in the range of 0.365-0.37. Therefore, when composite lithologic gangue is under the influence of water environment, when the water-immersion ratio is greater than 25%, its maximum strain has tended to be stable, and there is no need to worry about the problem of subsequent continuous increase in water-immersion ratio.
[0150] In the analysis of the crushing characteristics of waterlogged gangue, the crushing characteristics of a single waterlogged gangue are as follows: Fig.18 As shown in the figure, the crushing rates of oil shale and medium sandstone changed significantly before and after water intrusion. The crushing rate of oil shale after water intrusion was 0.25, which was 0.06 lower than that before water intrusion; the crushing rate of medium sandstone after water intrusion was 0.33, which was 0.18 higher than that before water intrusion. After water intrusion, the erosion effect of medium sandstone obviously made it easier to break, and the crushing rate in each particle size group was greater than that of the experimental group without water intrusion; while the oil shale was the opposite, and the crushing rate after water intrusion was lower than that before water intrusion. On the one hand, it was because the oil shale had a strong water absorption capacity, and the water in the gaps played a certain compressive capacity when the gangue was loaded, which reduced the crushing degree of the particles; on the other hand, the crushing degree of large-size gangue (20-30mm) of water-soaked oil shale was large, which filled the crushing gap of the other small-size groups, resulting in a low overall crushing rate.
[0151] The crushing characteristics of rock gangue during water immersion time are as follows: Fig.19 As shown in the figure, the crushing analysis of the immersion time of lithologic gangue is as follows: Fig. 20 As shown in the figure, from the time dimension, the crushing degree of composite lithology gangue will increase with the increase of immersion time, and its crushing rate is 0.2 for 0 days, 0.29 for 2 days, 0.36 for 5 days, and 0.37 for 10 days. The crushing rate of soaked gangue increases with the increase of immersion time, and the crushed particle size is mainly concentrated in the particle size range of 20mm-30mm. The crushing rate of 0-2 days and 2-5 days of immersion increased by 0.09 and 0.07 respectively, indicating that the composite rock gangue has the strongest water absorption and the largest change in anti-aging performance in the first 5 days of immersion. With the increase of immersion time, the strain and crushing rate of composite lithology gangue show a positive correlation, indicating that immersion will cause significant changes in the physical properties of gangue. From the perspective of particle distribution, the proportion of gangue with a particle size of 0mm-5mm gradually increases, which leads to an increase in crushing rate. From the perspective of the sample as a whole, the strain gradually increases and the compressive capacity weakens.
[0152] The crushing characteristics of the proportion of rock gangue soaked in water are as follows Fig.21 As shown in Figure 2, the crushing analysis of the proportion of lithologic gangue soaked in water is as follows: Fig. 22 As shown in the figure, from the spatial dimension analysis, the crushing rate is 0.26 when the proportion of water-soaked gangue is 25%, 0.33 when it is 50%, and 0.29 when it reaches 100%. When the proportion of water-soaked gangue reaches 50%, the crushing rate of composite lithologic gangue sample is the largest. This is because only 50% of the sample is soaked in water during loading, and some water will spread to the dry area without water. The gaps in the whole sample lack water filling, and the compressive capacity of 50% of the sample is greatly reduced after the gangue is soaked in water. Therefore, the experimental group with 50% water-soaked is more prone to crushing. When the proportion of water-soaked gangue reaches 100%, the crushing rate of composite lithologic gangue is 0.29, which is lower than that of the 50% experimental group. It can be seen that after the water-containing gangue is soaked in the whole sample, it also has a certain effect on reducing the crushing of the sample. When the proportion of water-soaked gangue reaches 25%, the crushing rate and strain increase significantly, and when the proportion of water-soaked gangue reaches 50%, the crushing rate and strain reach the peak. The strain and crushing rate of the experimental group with 100% water immersion were lower than those with 50% water immersion. It can be seen that when water molecules can fill the gaps in the gangue, a certain compressive effect can be achieved to reduce the crushing of the gangue.
[0153] The following conclusions were drawn: The selection of composite lithology gangue in the experiment included medium sandstone and oil shale, and the density of oil shale was measured to be 2.200 g / cm 3 , the bulk density is 1.244g / cm 3 ; The density of medium sandstone is 2.480g / cm 3 , bulk density is 1.325g / cm 3The water content of oil shale after 0 days of immersion in water is 0%, 6.57% after 2 days, 7.12% after 5 days, and 7.22% after 10 days; the water content of medium sandstone after 0 days of immersion in water is 0%, 14.66% after 2 days, 16.11% after 5 days, and 16.22% after 10 days. Physical experiments show that oil shale has a small density and strong water absorption, and it is mostly flaky after being broken; medium sandstone has a large density and weak water absorption, and it is mostly blocky after being broken. The physical properties of the two types of gangue are obviously different.
[0154] From the optimization experiment of composite lithology gangue ratio, it can be seen that the bearing capacity of oil shale is better than that of medium sandstone, but its degree of crushing is higher than that of medium sandstone. Through the optimization experiment of maximum particle size (20mm, 30mm), it can be seen that the strain difference of medium sandstone is 0.3%, and the difference of oil shale is 0.1%, indicating that the maximum particle size of 20mm and 30mm has little difference in the bearing capacity of gangue; through the gradation optimization experiment, it can be seen that the gradation of 0.4 and the strain of 0.285 are the optimal gradation; in the optimization experiment of composite lithology gangue, it is found that the bearing capacity of the sample increases with the increase of the proportion of oil shale, among which 0mm~10mm, 15mm~20mm are oil shale, 10mm~15mm, 20mm~30mm are medium sandstone, and the strain of the A2 experimental group is the smallest, which is 0.27, which is the optimal ratio in the experiment. When oil shale is used as the fine material for particle filling, the strain is reduced by 0.015, which has better compressive resistance, and the crushing rate is reduced by 7%, which reduces the crushing degree of gangue. Therefore, in the proportion of composite lithology, special attention should be paid to the proportion of hard gangue in small particle size, so as to improve the bearing capacity of the filling body.
[0155] From the immersion time experiment, it can be seen that the bearing capacity of the gangue is weakened with the immersion time, and the strain increased by 0.07 and the crushing rate increased by 9% in the first two days of immersion. It is the stage with the greatest change in the bearing capacity and anti-aging performance of the gangue, and the crushing rate is positively correlated with the strain. The difference between the strain and crushing rate after immersion for 5 days and 10 days is small, 0.001 and 1% respectively, indicating that the gangue reaches a stable state after 5 days of immersion. From the immersion ratio experiment, it can be seen that when the stress reaches 14MPa, the maximum strain tends to be stable compared with 20MPa, and the difference in immersion ratio is between 0.001 and 0.025. Therefore, when the mining depth is greater than 600 meters and the immersion ratio reaches 25%, the influence of the immersion ratio is reduced and there is no need to worry about the subsequent immersion.
[0156] The overburden structure of the deep composite lithology gangue filling mining strata is relatively intact, the degree of fragmentation is not high, and there is no obvious separation between the rock strata. The degree of curvature has a certain similarity. Therefore, the following assumptions are made when solving the sinking space of the thick sandstone surface: the first assumption is that the sinking curve of the rock stratum above the filling surface satisfies the similarity principle, that is, it has a similar function expression, and the sinking curve of each rock stratum can be obtained by linear change of the roof sinking curve; the second assumption is that the sinking space of each rock stratum is constant, such as Fig.23As shown, the rock layer movement model is constructed: the origin of each rock layer coordinate is located in the center of the rock layer, the x-axis is horizontally positive to the right, and the roof deflection is positive downward; l is the half length of the filling surface.
[0157] It is assumed that within the bending zone, the rock mass only deforms but does not change in volume. Based on the above assumption, when studying the surface movement law of the mining area, the movement law of the random medium can be simplified into a theoretical model. This model regards the rock mass between the mined coal seam and the surface as a series of particles of equal mass and uniform size, such as Fig.24 When the particle a1 in the first layer moves and a hole is created there, the probability of the particles a2 and b2 above it falling under the action of gravity is 1 / 2. If the particles in the second layer fall to fill the hole in the first layer, the probability of the particles a3, b3, and c3 in the third layer falling to fill the hole in the second layer is 1 / 4, 1 / 2, and 1 / 4 respectively. By analogy, the distribution of the probability of particle movement can be obtained, as shown in Fig.25 As shown. Fig.25 For example, any z value corresponds to a probability distribution histogram. Assuming that the particles are infinitely small, the histogram approaches the normal distribution probability density curve.
[0158] Assuming that the rock layer above the thick sandstone moves with the thick sandstone, the area S0 of the thick sandstone sinking after filling and mining is decomposed into a finite number of infinitely small units, and the surface movement is regarded as each small unit of the decomposition of area S0 The subsidence of the overlying rock layers caused by the subsidence of Fig.26 shown.
[0159] In order to verify the deep filling mining calculation model proposed in this invention, a model is constructed based on the coal mine drilling data to simulate the situation of unlimited mining in the horizontal coal seam and limited mining in the inclination. The coal seam is buried 725m and the mining thickness is 6m. The filling rate of the filling body is designed to be 100%. The secondary compression rate of the filling body is 34% due to the influence of high ground stress and water environment. At the same time, the mechanical parameters of each stratum and the filling body are determined by referring to relevant literature, and numerical simulation is performed using Flac2d to provide verification data for the calculation results of the mechanical model.
[0160] The direct top deflection is calculated using the relevant formula of the top plate mechanical model. The relevant parameters are as follows:
[0161] The equivalent deadweight load of the rock layer directly above the top is 20Mpa; ; Filling surface half length ; Affected by high ground stress and water environment, ; ; Get the direct top deflection function , The unknown coefficients are shown in Table 1.
[0162] Table 1 Undetermined coefficients of top plate deflection
[0163] ;
[0164] The direct top deflection solved is Fig. 27 As shown, the roof deflection calculated by the mechanical model of the present invention is a "U"-shaped curve, the maximum sinking point is located in the center of the goaf, and the value is 995mm. The maximum sinking value of the roof obtained by numerical simulation is 1010mm, so it can be considered that the established model is reasonable.
[0165] In the calculation of the subsidence space of extremely thick sandstone, It can be obtained from the internal sinking boundary curve function of the deep filling mining rock layer. Based on the established numerical simulation model, the distance between the sinking boundary point of each rock layer and the center of the goaf is extracted, and the functional relationship between the sinking boundary position and the distance from the coal seam is established;
[0166] The internal subsidence boundary of the rock stratum in deep filling mining of coal mines satisfies the following relationship:
[0167] ;
[0168] The fitting results of the sinking boundary and the distance from the coal seam are as follows: Fig.28 As shown in the figure, the subsidence of the thick sandstone was analyzed and calculated, and the results are as follows Fig.29 As shown. Fig.29 It can be seen that the thick sandstone subsidence space calculated by the mechanical model is similar to the roof deflection, both of which are "U" curves. The maximum subsidence point is located in the center of the goaf, with a value of 853mm. The maximum roof subsidence value obtained by numerical simulation is 863mm.
[0169] Based on the boundary angle data of the mining area, a functional relationship between the ratio of loose layer thickness to mining depth and the boundary angle was established:
[0170] ;
[0171] In the formula, y is the boundary angle, and the fitting results are as follows: Fig.30 shown.
[0172] In the calculation model of topsoil subsidence, the thickness of the rock layer above the thick sandstone Thick sandstone ; Surface movement boundary angle The calculated surface subsidence curve is as follows: Fig.31 As shown by the green line. Fig.31It can be seen that the calculated maximum surface subsidence point is located in the center of the goaf, with a value of 821 mm. The maximum surface subsidence obtained by numerical simulation is 840 mm. With the increasing distance from the coal seam, the subsidence value of each rock layer decreases continuously, and the subsidence influence range gradually increases, which is in line with the general law of surface subsidence in filling mining.
[0173] Based on Winkler's elastic foundation theory, the present invention solves the roof deflection of deep backfill mining. The calculated results differ from the results of numerical simulation by only 15 mm, and the model can be considered accurate and reliable. Based on the data of numerical simulation, the relationship between the internal sinking boundary of the rock stratum in deep backfill mining in coal mines and the distance from the top of the coal seam is established. Using this relationship, combined with similarity theory, a calculation model for the sinking space of the thick sandstone surface is derived. The calculated results differ from the numerical simulation by 10 mm, and the sinking space of the thick sandstone surface is solved more accurately.
[0174] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features may be replaced by equivalents, and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for predicting deep mining subsidence taking into account secondary compression of composite lithology gangue, characterized in that: Calculate the deflection of the overlying roof of the collapsed goaf and the filled goaf, obtain the settlement curve of the thick sandstone based on the similarity principle, and obtain the settlement curve of the topsoil layer by combining the random medium theory. Substitute the coordinate value of any point on the x-axis to obtain the corresponding settlement value of the topsoil layer to achieve settlement prediction; Based on the random medium theory, the corresponding topsoil subsidence values are obtained, including: assuming that the mining depth and width are infinitely small, the unit mining-induced Settlement value at point for: ; ; In the formula, express The depth value corresponding to the coordinate value, is the influence radius, is the particle size connection constant; For mining depth of the surface, , then it satisfies: ; ; ; In the formula, The mining depth is of the surface The settlement value corresponding to the coordinate value, is the main impact radius; The random medium theory considers the bending and sinking of thick sandstone as the mining of medium-shallow non-uniform coal seams, and regards the area of the sinking of thick sandstone as Decompose into a finite number of infinitely small units, and regard the surface movement as the area The subsidence of the ground caused by mining in each small mining unit is superimposed. The distance from the origin on the axis is ,exist The distance from the origin on the axis is , the sinking curve of the topsoil layer for: ; In the formula, The thickness of the rock layer above the thick sandstone. The thickness of the sandstone is very thick. It is the sinking curve of the extremely thick sandstone. Move the boundary angle for the surface.
2. The deep mining subsidence prediction method taking into account the secondary compression of composite lithology gangue according to claim 1 is characterized in that: The calculation of the deflection of the overlying roof of the collapsed goaf and the filled goaf includes: the deflection curve of the overlying roof of the filled goaf is: , the deflection curve of the overlying roof in the collapsed goaf is : ; ; In the formula, is half the length of the filling surface, is the bending stiffness of the roof, and the load of the rock layer from the top of the roof to the surface is called the equivalent deadweight load acting on the top of the roof , is the elastic coefficient of the filling body, is the elastic coefficient of coal, For the point Coordinates on the axis.
3. The deep mining subsidence prediction method taking into account the secondary compression of composite lithology gangue according to claim 2 is characterized in that: Solution and : ; ; ; ; In the formula, is a natural constant, is the characteristic coefficient of the filling body, is the characteristic coefficient of coal body, , , , , , , , There are 8 undetermined coefficients.
4. The method for predicting deep mining subsidence taking into account secondary compression of composite lithology gangue according to claim 3 is characterized in that: The equations and boundary conditions for rotation, bending moment, and shear are combined to solve for the top plate deflection.
5. The method for predicting deep mining subsidence taking into account secondary compression of composite lithology gangue according to claim 4, characterized in that: The equations for rotation angle, bending moment and shear force include: The rotation angle equation below the overlying roof in the filling goaf is: The bending moment equation is The shear force equation is , the rotation angle equation below the overlying roof of the collapsed goaf is The bending moment equation is The shear force equation is : ; ; ; ; ; 。 6. The method for predicting deep mining subsidence taking into account secondary compression of composite lithology gangue according to claim 5, characterized in that: The boundary conditions include: condition 1, At infinity of the axis, the roof deflection is equal to the compression of the coal body: ; From condition 1, we can get .
7. The method for predicting deep mining subsidence taking into account secondary compression of composite lithology gangue according to claim 6, characterized in that: Boundary conditions include: Condition 2, when the filling body in the mining area is fully compacted: ; 。 8. The method for predicting deep mining subsidence taking into account secondary compression of composite lithology gangue according to claim 7, characterized in that: The boundary conditions include: Condition 3: At the same time, at the connection between the filling body and the coal body, the following continuity conditions exist: ; ; ; ; The eight unknown coefficients were obtained by solving the simultaneous equations, and the deflection of the overlying roof in the collapsed goaf and the filled goaf was calculated.
9. The method for predicting deep mining subsidence taking into account secondary compression of composite lithology gangue according to claim 8, characterized in that: The subsidence curve of extremely thick sandstone is: ; ; In the formula, is the horizontal coordinate transformation coefficient of the thick sandstone subsidence curve relative to the roof subsidence curve, is the horizontal coordinate of the roof subsidence boundary, is the horizontal coordinate of the boundary of the thick sandstone subsidence. and The top plate deflection is obtained by combining the two curves. .